Characterization of Microvesicles in Septic Shock Using High-Sensitivity Flow Cytometry. Issue 4 (October 2016) - Lehner, Georg Franz; Harler, Ulrich; Haller, Viktoria Maria; Feistritzer, Clemens; Hasslacher, Julia; Dunzendorfer, Stefan; Bellmann, Romuald; Joannidis, Michael
Abstract : Supplemental Digital Content is available in the text Abstract: Purpose: Endothelial pathology is considered to play a key role in septic shock. Since endothelial-derived microvesicles (MV) are elevated in various diseases associated with endothelial pathology, they are considered surrogate markers of the endothelial state. By analyzing the signature of circulating MV with high-sensitivity flow cytometry (hsFC), we wanted to test the hypothesis whether endothelial-derived MV are increased in septic shock. Methods: MV in blood from healthy volunteers and patients with septic shock treated in a medical intensive care unit were quantified by hsFC, which has an improved detection limit of approximately 0.3 μm. Results: Patients with septic shock (n = 30) showed 3-fold higher levels of CD31+/CD41− MV (58.5 (26.4–101.2) [median (25th–75th percentile)] vs. 19.5 (12.8–25.4) MV/μL; P <0.001) compared with healthy volunteers (n = 18). Absolute counts of CD144+, CD62E+, and CD106+ MV, specific for endothelial-derived MV, were low in all groups. The number of CD31+/CD41− MV correlated significantly with leukocyte count ( r s = 0.64; P <0.001). Platelet-derived CD41+ MV were significantly elevated in the group dying within 48 h after inclusion (639.1 (321.3–969.7) vs. 221.5 (119.5–456.9) MV/μL; P = 0.037). Patients dying within 48 h had also significantly higher levels of CD31+/CD41−/AnnexinV− MV (51.9 (24.9–259.8) vs. 18.9 (9.7–31) MV/μL; P = 0.028). Conclusions: Despite an improved detection limit for MV by using hsFC, counts of endothelial-specific MV are unexpectedly low in patients with septic shock. Increased amounts of CD41+ and CD31+/CD41−/AnnexinV− MV indicate release by activated platelets and possibly leukocytes correlating with unfavorable outcome.